Glossary of Administrative Term (English-Hindi) (New Delhi Commission for Scientific and Technical Terminology, 2008)
This is a Specialized Dictionary for Administrative Terminology. It is a English-Hindi Dictionary.
Keywords: Dictionary for Administrative Terminology; English-Hindi Dictionary